2011
DOI: 10.1007/s12671-011-0072-3
|View full text |Cite
|
Sign up to set email alerts
|

The Turkish Version of Mindful Attention Awareness Scale: Preliminary Findings

Abstract: The Mindful Attention Awareness Scale (MAAS) is the most frequently utilized self-report measure of mindfulness. The present study sought to investigate the psychometric properties of MAAS among non-clinical Turkish participants as well as to explore the relationships between mindfulness and well-being, experiential avoidance, cognitive reappraisal, and impulsivity. One hundred participants from two samples were recruited for the study. After the translation of MAAS into Turkish, a test battery including MAAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 36 publications
7
28
0
1
Order By: Relevance
“…Parallel to findings for the original MAAS (Brown and Ryan 2003) and other translations of the scale (Deng et al 2012;Catak 2012;Jermann et al 2009), no gender differences in scale scores were found. The present study also found no differences in scale scores among adult students at several levels of education, suggesting that the Estonian MAAS may be used among a variety of adult normative populations.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Parallel to findings for the original MAAS (Brown and Ryan 2003) and other translations of the scale (Deng et al 2012;Catak 2012;Jermann et al 2009), no gender differences in scale scores were found. The present study also found no differences in scale scores among adult students at several levels of education, suggesting that the Estonian MAAS may be used among a variety of adult normative populations.…”
Section: Discussionsupporting
confidence: 59%
“…These subjective well-being indicators have similarly been used to assess the validity of the MAAS in other translations of the MAAS, such as the Turkish (Catak 2012) and Greek versions (Mantzios et al 2013). The variables associated with mindfulness in the present study represent important domains of personal and interpersonal wellbeing.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, their findings showed that neither the frequency of informal nor formal meditation practice was predictive of neither post course individual subscales nor total FFMQ score and the entire duration of formal meditation practice did not significantly predict post course FFMQ subscales or total scores. Catak (2012) investigated the psychometric properties of the MAAS in the Turkish population and explored the relationships of mindfulness with other related psychological constructs. His results showed that the Turkish version of MAAS possesses good psychometric qualities and good internal consistency.…”
Section: Review Of Literaturementioning
confidence: 99%
“…1 CONICET (Consejo Nacional de Investigaciones Científicas y Técnicas), Mar del Plata, Argentina 2 Universidad Nacional de Mar del Plata, Mar del Plata, Argentina recently, Turkey (Catak, 2012) and China (Deng et al, 2012). It has also been adapted for use with adolescents (Brown et al, 2011;de Bruin, Zijlstra, de Weijer-Bergsma, & Bögels, 2011) and psychiatric patients (Jermann et al, 2009).…”
Section: Research-article2013mentioning
confidence: 99%